Lichtenstein-type hernioplasty.: Preliminary analysis - Santandreu, Jorge; Vitancurt, Gustavo; Figoli, Luis; Moure, Luis; Barrios, Eugenio (Cirugía del Uruguay, 1996)
The preliminary analysis of a prospective hospital series concerned with 74 Lichtenstein-type herniop/asties invo/ves very low morbidity, a rapid occupational reentry by patients and ni/ incidence of recurrence; these data coincide with international reports. A more extensive series and long-related fo/low-up wi/1 underlie forthcoming communications by the present authors.